2013
DOI: 10.1097/hnp.0b013e3182a72c5a
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of “Steps to Surgical Success” (STEPS)

Abstract: This empirical study found that a holistic perioperative program significantly reduced patient pain and anxiety about surgery. Modalities included guided imagery, eye pillow, aromatherapy, and a written personal healing plan. Nurses are in a prime position to deliver these interventions, given their frequent direct contact with patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 9 publications
0
1
0
1
Order By: Relevance
“…(biberiye), Crocus sativus L. (safran) gibi uçucu yağların, müdahale gruplarında ya da kontrol, plasebo gruplarında kullanılan aromatik yağlar olduğu görülmüştür. [50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67] Aromaterapide kullanılan, anksiyolitik etkileri değerlendirilen diğer uçucu yağlarla yapılan çalışmalar Tablo 3'te verilmiştir.…”
Section: Papatya Uçucu Yaği Ve Anksi̇yeteunclassified
“…(biberiye), Crocus sativus L. (safran) gibi uçucu yağların, müdahale gruplarında ya da kontrol, plasebo gruplarında kullanılan aromatik yağlar olduğu görülmüştür. [50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67] Aromaterapide kullanılan, anksiyolitik etkileri değerlendirilen diğer uçucu yağlarla yapılan çalışmalar Tablo 3'te verilmiştir.…”
Section: Papatya Uçucu Yaği Ve Anksi̇yeteunclassified
“…A further study, which was however non-controlled and of poor methodological quality, examined an extensive, multimodal, and holistic approach to reducing pain that consisted of multiple preoperative interviews and a combination of several of the therapies mentioned above (11). Even though the study found a significant reduction in pain (of -1.19 points, on a scale of 1 to 10, p<0.001), it is not very meaningful for everyday clinical practice due to methodological shortcomings and a questionable feasibility (as it carries high financial and time expenses).…”
Section: Postoperative Painmentioning
confidence: 99%